PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA - Reni Setyaningsih; Zulfan Hanif Rahman (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The low problem solving ability possessed by students is the background of this research. This study aims to test the positive effect of the problem-based learning model on the problem-solving skills of fourth-grade students at State Elementary School Mojoduwur II. This study used the quasi-experimental method and a pretest-posttest control group design. The sample was 50 students determined with cluster random sampling. Data were collected using a problem-solving skill test with 5 post-test questions and 5 pre-test questions. The hypothesis was tested using a t-test. The results showed that there was a positive effect of the use of the problem-based learning model on the student’s problem-solving skills with a significance value of <0.05 so that Ha is accepted. In addition, the results of the study also showed that students in the experimental class experienced a greater average increase when compared to the control class.